Spectral analysis of IGR J01572−7259 during its 2016 outburst. Issue 1 (21st December 2017) - La Palombara, N; Esposito, P; Mereghetti, S; Pintore, F; Sidoli, L; Tiengo, A
Abstract: We report on the results of the XMM–Newton observation of IGR J01572−7259 during its most recent outburst in 2016 May, the first since 2008. The source reached a flux f ∼ 10 −10 erg cm −2 s −1, which allowed us to perform a detailed analysis of its timing and spectral properties. We obtained a pulse period P spin = 11.58208(2) s. The pulse profile is double peaked and strongly energy dependent, as the second peak is prominent only at low energies and the pulsed fraction increases with energy. The main spectral component is a power-law model, but at low energies, we also detected a soft thermal component, which can be described with either a blackbody or a hot plasma model. Both the EPIC and RGS spectra show several emission lines, which can be identified with the transition lines of ionized N, O, Ne, and Fe and cannot be described with a thermal emission model. The phase-resolved spectral analysis showed that the flux of both the soft excess and the emission lines vary with the pulse phase: the soft excess disappears in the first pulse and becomes significant only in the second, where also the Fe line is stronger. This variability is difficult to explain with emission from a hot plasma, while the reprocessing of the primary X-ray emission at the inner edge of the accretion disc provides a reliable scenario. On the other hand, the narrow emission lines can be due to the presence of photoionized matter around the accreting source.